Tinjauan Fatwa Dewan Syariah Nasional No: 75/Dsn-MUI/VII/2009 Terhadap Penjualan Langsung Berjenjang Syariah Di Tiens Syariah - Suhardiman Izini (Universitas Islam Lamongan, 2018)
In muamalah activity, Islam has provided a clear line of wisdom. Business or trade transactions are things that are highly regarded and glorified in Islamic teachings, whether done individually or in groups. The attention of Islam towards trading transactions has recently been responded positively by Muslims in the world, particularly in Indonesia. Sharia institutions have shown fast development marked by the growing number and variety of Sharia-labeled businesses. Multi-level marketing has also been affected by Muslims’ awareness of sharia-based behaviors in their daily lives. This has also been supported by the issuance of the fatwa from DSN MUI (Sharia National Council – Indonesian Ulama Council) No. 75/DSN-MUI/VII/2009 concerning Sharia multi-level direct selling (PLBS). This phenomenon has urged Tiens Indonesia to adjust their network system to the stipulations in the fatwa. This study aimed to analyze and describe as well as evaluate the network system applied by Tiens Syariah. Using the descriptive qualitative field study, the research is conducted in Yogyakarta Special Province. Data is gathered from observation, interview, and documentation. The obtained data was then analyzed qualitatively and explained descriptively. The result of research shows that based on Point 12 of the fatwa from DSN-MUI No. 75 Year 2009 concerning Sharia multi-level direct selling, the multi-level marketing company Tiens Syariah has fulfilled all the standards in Point 12. Therefore, the trading and network system of Tiens Syariah has been in line with the fatwa. Keywords: Sharia National Council fatwa, Shariah Gradual Direct Selling, Tiens Syariah